Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
b) \(\frac{2^9.4^{10}}{8^8}=\frac{2^9.\left(2^2\right)^{10}}{\left(2^3\right)^8}=\frac{2^9.2^{20}}{2^{24}}=\frac{2^{29}}{2^{24}}=2^5=32.\)
Chúc bạn học tốt!
![](https://rs.olm.vn/images/avt/0.png?1311)
a: =>x-8/5=1/20-1/10=-1/20
=>x=-0,05+1,6=1,55
b: =>x-3/2=4/3 hoặc x-3/2=-4/3
=>x=17/6 hoặc x=1/6
c: =>\(\left|x-\dfrac{1}{3}\right|=\dfrac{5}{2}-\dfrac{1}{4}+\dfrac{2}{3}=\dfrac{35}{12}\)
=>x-1/3=35/12 hoặc x-1/3=-35/12
=>x=39/12=13/4 hoặc x=-31/12
d: =>|x-5/8|=3/4
=>x-5/8=3/4 hoặc x-5/8=-3/4
=>x=11/8 hoặc x=-1/8
![](https://rs.olm.vn/images/avt/0.png?1311)
a) Ta có: \(\frac{3}{8}-\frac{1}{5}+\frac{3}{40}\)
\(=\frac{15}{40}-\frac{8}{40}+\frac{3}{40}\)
\(=\frac{10}{40}=\frac{1}{4}\)
b) Ta có: \(\frac{21}{4}\cdot\frac{3}{8}+\frac{43}{4}\cdot\frac{3}{8}-4\cdot\frac{1}{2}\)
\(=\frac{3}{8}\left(\frac{21}{4}+\frac{43}{4}\right)-2\)
\(=\frac{3}{8}\cdot16-2\)
\(=6-2=4\)
c) Ta có: \(\frac{-5}{9}+\frac{7}{15}+\frac{-2}{11}+\frac{4}{-9}+\frac{8}{15}\)
\(=\left(\frac{-5}{9}+\frac{-4}{9}\right)+\left(\frac{7}{15}+\frac{8}{15}\right)+\frac{-2}{11}\)
\(=-1+1+\frac{-2}{11}\)
\(=\frac{-2}{11}\)
d) Ta có: \(125\%\cdot\left(\frac{-1}{2}\right)^2:\left(1\frac{5}{6}-1.5\right)+2016^0\)
\(=\frac{5}{4}\cdot\frac{1}{4}:\left(\frac{11}{6}-\frac{3}{2}\right)+1\)
\(=\frac{5}{16}\cdot3+1\)
\(=\frac{15}{16}+\frac{16}{16}=\frac{31}{16}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\left(\frac{3}{7}-\frac{5}{2}-\frac{3}{5}\right)-\left(-\frac{4}{7}-\frac{3}{2}+\frac{2}{5}\right)=\frac{3}{7}-\frac{5}{2}-\frac{3}{5}+\frac{4}{7}+\frac{3}{2}-\frac{2}{5}\)
\(=\left(\frac{3}{7}+\frac{4}{7}\right)+\left(-\frac{5}{2}+\frac{3}{2}\right)+\left(-\frac{3}{5}-\frac{2}{5}\right)\)
\(=1+\left(-1\right)+\left(-1\right)\)
\(=-1\)
Hok tốt nha^^
giup voi
a) \(\frac{8^5.27^3}{6^9.4^4}=\frac{\left(2^3\right)^5.\left(3^3\right)^3}{2^9.3^9.\left(2^2\right)^4}=\frac{2^{15}.3^9}{2^9.3^9.2^8}=\frac{2^{15}.3^9}{2^{17}.3^9}=\frac{1}{2^2}=\frac{1}{4}\)
b) \(\left(\frac{-2}{3}\right)^3:\frac{8}{3}-\left|-\frac{5}{3}\right|=\frac{-8}{27}:\frac{8}{3}-\frac{5}{3}\)
\(=-\frac{1}{9}-\frac{5}{3}=-\frac{1}{9}-\frac{15}{9}=-\frac{16}{9}\)